Experiment and 3D-numerical studies on soft clay bed reinforced with different types of cellular confinement systems. (March 2017) - Hegde, A.; Sitharam, T.G.
Abstract: The manuscript deals with the experimental and 3-dimensional numerical studies carried on the soft clay bed reinforced with three different types of 3D-cellular confinement systems. The geogrid cells, commercial geocells and the bamboo cells are the three different types of 3D-cells used in the study. First, laboratory plate load tests were performed on the soft clay beds. Subsequently, numerical simulations were carried out to compliment the experimental findings. The numerical simulations were carried out in 3-dimensional framework using FLAC 3D by considering the actual honeycomb shape of the geocells. The foundation soil, infill soils and the cell materials were modeled with three different material models, namely, modified Cam-clay, Mohr Coulomb and the linear elastic models. The maximum bearing capacity was observed in the case of foundation bed reinforced with the bamboo cells due to its higher stiffness, higher tensile strength and the higher surface roughness values. Using the validated numerical model, the effect of tensile strength and the surface roughness of the geocell on the performance of the reinforced soft clay beds were quantified. The tensile strength of the geocell material found to have a more pronounced influence than the surface roughness. In addition, a hypothetical case of the prototype foundation on the soft clay has been analyzed and results of the model and prototype cases were found to be in accordance with each other.